Ingestion of microplastics by nematodes depends on feeding strategy and buccal cavity size. (December 2019) - Fueser, Hendrik; Mueller, Marie-Theres; Weiss, Linette; Höss, Sebastian; Traunspurger, Walter
Abstract: Microplastics are hardly biodegradable and thus accumulate rather than decompose in the environment. Due to sedimentation processes, meiobenthic fauna is exposed to microplastics. Within the meiofauna, nematodes are a very abundant taxon and occupy an important position in benthic food webs by connecting lower and higher trophic levels. However, the key determinants of the uptake of microplastics by freshwater nematodes are still unknown. To investigate the bioaccessibility of microplastics for nematodes, we performed single- and multi-species ingestion experiments in which the ability of seven nematode species (six bacterial and one fungal feeder), diverse in their buccal cavity morphology (1.3–10.5 μm), to ingest fluorescence-labelled polystyrene (PS) beads along with their natural diet was examined. Applied beads sizes (0.5, 1.0, 3.0 and 6.0 μm), exposure time (4, 24 and 72 h) and concentration (3 × 10 6  PS beads ml −1 and 10 7  PS beads ml −1 ) were varied. Ingested beads were localized and quantified via fluorescence microscopy in the nematodes. In contrast to fungal-feeding nematode species with a stylet, bacterial-feeding species ingested 0.5- and 1.0-μm PS beads with up to 249 and 255 beads after 24 h, respectively. Microplastics ≥0.5 μm could only be ingested and transported into the gastrointestinal tract, if the buccal cavities were considerably (>1.3 times) larger than the beads. At concentrations of 10 7  PS beads ml −1 ingestion rates were influenced by exposure time and PS bead concentration. In case of a known microplastic size distribution in the environment, predictions on the potential ingestion for nematode communities can be made based on the feeding type composition and the size of their buccal cavities. Graphical abstract: Image 1 Highlights: Polystyrene beads >0.5 μm can only be ingested by nematodes with a buccal cavity. Size ratio of buccal cavity to beads can predict the ingestion potential of beads. The buccal cavities strongly limited the ingestion of beads at a ratio of 1.3–3.6. The ingestion of different bead sizes was found to be species-specific. Exposure time and bead concentration influenced the ingestion rates of beads. Abstract : Ingestion and gastrointestinal transport of PS beads by bacterial-feeding nematodes is determined by the ratio of particle to buccal cavity size.